PEMANFAATAN MOL SUBSTRAT EKSTRAK LENGKUAS DENGAN BERBAGAI SUMBER INOKULAN TERHADAP PERTUMBUHAN, INDEK PANEN DAN KUALITAS SAWI HIJAU (Brassica chinensis var. parachinensis) - frisqilayanti frisqilayanti; Agus Sugianto; Anis Sholihah (AGRONISMA, 2021)
As time goes by and the increasing population, the need for horticultural crops in Indonesia, especially vegetables, is getting higher because the demand for healthy vegetables is increasing as well. Mustard greens are vegetables that are very popular with the community, besides being delicious, they also contain many benefits. The use of organic matter in farming not only maintains the quality of the harvest but will fertilize the soil and improve soil structure in the long term. This study aims to determine the effect of MOL concentration of galangal extract substrate with various inoculant sources on the growth and quality of mustard greens (Brassica chinensis var. parachinensis.               This research was conducted from April to May 2021, located in Randuagung Gondang Tengah Hamlet, Singosari District, Malang Regency with an altitude of 400-700 m above sea level, an average temperature of 22°-32°C and rainfall of 349 mm/year. This experiment was conducted in a factorial completely randomized design (CRD) with controls. Factor I: MOL concentration of galangal extract substrate (L) consists of 4 levels L1 = 20%, L2 = 3 0%, L3 = 40% and L4 = 50%. Factor II: Inoculant source (K) consisting of 3 levels K1 = chicken manure, K2 = goat manure and K3 = cow manure. The treatment combinations were 12 plus 1 control treatment so that there were 13. Each treatment combination was repeated 3 times and each treatment had 3 samples so that treatment: 13 x 3 x 3 = 117 plants. The data obtained were analyzed using analysis of variance (ANOVA) followed by a further test of the difference between the honest real test (BNJ) level of 5%.               The results showed that there was no significant interaction between the MOL concentration treatment of galangal extract substrate and various sources of inoculants on plant growth, namely plant length and number of leaves, but separately there was an effect at 21 DAP, where treatments L3 = 40% and L4 = 50% showed the same response was 26.68 cm and 30.58 cm, respectively. The K3 treatment = cow manure showed the longest response of 31.24 cm compared to the treatment of other inoculant sources. The highest harvest index was shown by the L3K1 treatment of 99.91%, as well as the MOL concentration of galangal extract substrate with various inoculant sources did not show an interaction with the quality parameters of chlorophyll and vitamin C content, but separately the significant effect occurred only in the treatment of the inoculant source K3 = fertilizer cowshed to the vitamin C content of mustard plants that is equal to 20.24 mg/100 g.